2017 International Conference on Military Technologies (ICMT) 2017
DOI: 10.1109/miltechs.2017.7988742
|View full text |Cite
|
Sign up to set email alerts
|

Towards a verification and validation test framework for open system architectures

Abstract: Today's military platforms are equipped with variety of sensors and effectors. However, these components are rarely interconnected or are only linked via manufacturer-specific, proprietary interfaces. This hinders changes to and extensions of platform components. Often platform modifications are only possible with the help of the original integrator, which complicates a seamless integration of new components. In order to unify the interfaces of sub-systems and enhance platform interoperability, several open ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…In addition, STANAG 4754 also cover other aspects of the vehicle infrastructure. These include safety (NATO, 2018c), verification and validation (Ota et al, 2017) and Crew Terminal Software Architecture (CTSA) (NATO, 2018d). The CTSA aims at defining a standard Inter-Process Communication interface and the nature of its deployment in alignment with Crew Terminal hardware, so that CT software modules can be made portable and re-usable.…”
Section: Nato Generic Vehicle Architecturementioning
confidence: 99%
“…In addition, STANAG 4754 also cover other aspects of the vehicle infrastructure. These include safety (NATO, 2018c), verification and validation (Ota et al, 2017) and Crew Terminal Software Architecture (CTSA) (NATO, 2018d). The CTSA aims at defining a standard Inter-Process Communication interface and the nature of its deployment in alignment with Crew Terminal hardware, so that CT software modules can be made portable and re-usable.…”
Section: Nato Generic Vehicle Architecturementioning
confidence: 99%
“…Various studies have been and are still being conducted on methods and approaches for evaluating whether systems actually embrace MOSA principles as reported by Gaska in (Gaska 2012), Rendon in (Rendon 2008), and Guertin in (Guertin 2017). Additionally, various authors have also reported on interface evaluation methods for open systems architectures (Colombi 2015, Burger 2014, the development of a MOSA decision support tool (Dai 2022), and a test framework for verification and validation of open systems architectures (Ota 2017). Although most of this research work involves the development of multiple ways in which systems can be evaluated for MOSA compliance, none adequately addresses the evaluation of architectures and architecture requirements prior to system design.…”
Section: Introductionmentioning
confidence: 99%